Risk Factors for Type 2 Diabetes Mellitus in the Productive Age Group (20-44 Years) - Fin, Fin; Suhadi, Suhadi; Azim, La Ode Liaumin (RRZ Scientific Publishing, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood sugar levels. Globally, the average age of people with diabetes is 40 years. In Indonesia, diabetes is a gap with the highest incidence in the 20-44 year age group. Southeast Sulawesi recorded an increase in diabetes cases from 2022 to 2023, and the Lepo-Lepo Health Center reported 266 cases in 2022 and 360 cases in 2023. Meanwhile, in 2024 from January to July, the 20-44 year age group had 95 cases, where hereditary factors and obesity usually cause a high incidence of diabetes. This study aimed to identify risk factors for diabetes in the productive age in the Lepo-Lepo Health Center work area in 2024. The design of this study was a case-control study with the matching method, and the number of people with diabetes was 95. Sampling was performed using the purposive method, and then the calculation was carried out to obtain 41 pairs of case and control samples. The statistical test used was McNemar. The results showed that the obesity variable had an OR of 4,250 and a hereditary history 11,000. So it can be concluded that obesity and hereditary history were risk factors for Diabetes Mellitus in the productive age (20-44 years) in the Lepo-Lepo Health Center work area in 2024. Community-based preventive efforts targeting individuals with obesity and a family history of diabetes are strongly recommended to reduce the risk of diabetes mellitus in the productive age group